Payment of Zakat on Income and Services: The Behavior and Characteristics of Millennial Employees in Jakarta and West Java Province - Miryati Safitri; Achmad Firdaus; Ahmad Levi Fachrul Avivy; Muhammad Hasbi Zaenal (International Journal of Zakat, 2022)
This study aims to analyze the factors of millennial employees in DKI Jakarta and West Java in paying zakat on income and services. This study covers the behavioural variables of millennial employees which include zakat literacy, the influence of social media and religiosity as well as other millennial employee characteristics, namely education level, type of zakat recipient institution selected, frequency of zakat payments, and experience in zakat. The millennial working population is represented by residents aged 20 - 39 years. The distribution of the questionnaire was carried out via google form to 400 people in DKI Jakarta and West Java as respondents. Data analysis using SEM PLS with the results of decisions to pay zakat income and services by millennial employees in the two provinces is influenced by social media and religiosity factors. Information about zakat on social media is believed by the millennial generation and so is the literacy factor regarding the amount of zakat and the conditions for zakat. Then other influences are the level of education, type of zakat payment preference institution, frequency of zakat payments, routine of attending recitations and experience in giving zakat which is believed to influence the decision to pay zakat income and services